Simultaneous Separation of Antioxidants and Carbohydrates From Food Wastes Using Aqueous Biphasic Systems Formed by Cholinium-Derived Ionic Liquids - Neves, Catarina M. S. S.; Figueiredo, Marcos; Reis, Patrícia M.; Sousa, Ana C. A.; Cristóvão, Ana C.; Fiadeiro, Mariana B.; Rebelo, Luís Paulo N.; Coutinho, João A. P.; Esperança, José M. S. S.; Freire, Mara G. (Frontiers in Chemistry, 2019)
The food industry produces significant amounts of waste, many of them rich in valuable compounds that could be recovered and reused in the framework of circular economy. The development of sustainable and cost-effective technologies to recover these value added compounds will contribute to a significant decrease of the environmental footprint and economic burden of this industry sector. Accordingly, in this work, aqueous biphasic systems (ABS) composed of cholinium-derived bistriflimide ionic liquids (ILs) and carbohydrates were investigated as an alternative process to simultaneously separate and recover antioxidants and carbohydrates from food waste. Aiming at improving the biocompatible character of the studied ILs and proposed process, cholinium-derived bistriflimide ILs were chosen, which were properly designed by playing with the cation alkyl side chain and the number of functional groups attached to the cation to be able to create ABS with carbohydrates. These ILs were characterized by cytotoxicity assays toward human intestinal epithelial cells (Caco-2 cell line), demonstrating to have a significantly lower toxicity than other well-known and commonly used fluorinated ILs. The capability of these ILs to form ABS with a series of carbohydrates, namely monosaccharides, disaccharides and polyols, was then appraised by the determination of the respective ternary liquid-liquid phase diagrams at 25 °C. The studied ABS were finally used to separate carbohydrates and antioxidants from real food waste samples, using an expired vanilla pudding as an example. With the studied systems, the separation of the two products occurs in one-step, where carbohydrates are enriched in the carbohydrate-rich phase and antioxidants are mainly present in the IL-rich phase. Extraction efficiencies of carbohydrates ranging between 89% and 92% to the carbohydrate-rich phase, and antioxidant relative activities ranging between 65% and 75% in the IL-rich phase were obtained. Furthermore, antioxidants from the IL-rich phase were recovered by solid-phase extraction, and the IL was recycled for two more times with no losses on the ABS separation performance. Overall, the obtained results show that the investigated ABS are promising platforms to simultaneously separate carbohydrates and antioxidants from real food waste samples, and could be used in further related applications foreseeing industrial food waste valorization.